PENGARUH STRUKTUR KEPEMILIKAN, UKURAN PERUSAHAAN, DAN CAPITAL INTENSITY TERHADAP EFFECTIVE TAX RATE (ETR) (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2011-2013) - Mohammad Danu Bachtiar; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2015)
This study aims to examine empirically the influence of ownership structure (managerial ownership, institutional ownership, public ownership), firm size, and capital intensity to effective tax rate (ETR). The population of this research was all companies listed on the Indonesia Stock Exchange in the period 2011-2013. Sampling was done by using purposive sampling method. There were 137 companies that fulfilled the criteria of sampling. This study used multiple linear regression analysis to examine the influence of independent variables on the dependent variable. The results of this study showed that the variable of public ownership have negative significant influence to the effective tax rate. Capital intensity showed a positive significant relationship to the effective tax rate. Meanwhile variable managerial ownership, institutional ownership and firm size did not significantly influence the effective tax rate.